Long-acting slow effective release antiretroviral therapy. (2nd November 2017) - Edagwa, Benson; McMillan, JoEllyn; Sillman, Brady; Gendelman, Howard E
ABSTRACT: Introduction : Advances in long-acting antiretroviral therapy (ART) can revolutionize current HIV/AIDS treatments. We coined the term 'long-acting slow effective release ART' (LASER ART) to highlight the required formulation properties of slow drug dissolution, poor water-solubility, bioavailability, little-to-no off-target toxicities and improved regimen adherence. Drug carrier technologies characterized by high antiretroviral drug (ARV) payloads in a single carrier improve the pharmacokinetic and pharmacodynamic profiles. The surface modifications of ARV carriers target monocyte-macrophages and facilitate drug transport across physiological barriers and to virus-susceptible CD4 + T cells. Areas covered : The review highlights developments of reservoir-targeted LASER ART for improved therapeutic outcomes. Such nanoART delivery platforms include decorated multifunctional nano- and micro-particles, prodrugs and polymer conjugates. Therapeutic strategies such as gene-editing technologies boost ART effectiveness. Expert opinion : The persistence of HIV-1 in lymphoid, gut and nervous system reservoirs poses a challenge to viral eradication. Emerging slow-release drug carriers can target intracellular pathogens, activate antiviral immunity, promote genome editing, sustain drug depots and combine therapeutics with image contrast agents, and can meet unmet clinical needs for HIV-infected patients. Such efforts will bring the medicines to reservoir sites and accelerate viral clearance.